Supervision of the Notary Supervisory Board on the Use of First Copies as a Substitute for Minutes of Deeds - Agung Iriantoro; Rizka Novilawati; Paul Atagamen Aidonojie; Leonid Juryi Galchynsky (APPTHI, 2025)
The notary public is a government official who bears a significant responsibility in the drafting and safekeeping of the original draft of an authentic deed. However, in practice, there are still notaries facing the loss or damage of such original drafts, which potentially undermines the integrity of legal evidence and the trust of the parties involved. This study employs a normative legal research method, utilizing an analytical approach with primary and secondary legal materials, focusing on statutory regulations. The research findings demonstrate that the Supervisory Council of Notaries carries a substantial responsibility in overseeing the issuance of replacement minutes to ensure that this process does not raise any legal uncertainties and continues to safeguard the document’s security. The comprehensive supervision by Supervisory Council of Notaries involves validating the authenticity of the copied document, assessing procedural propriety, issuing recommendations, and making administrative decisions. Furthermore, the status of the first copy used as a basis for issuing an authentic replacement minute holds an equivalent legal standing to the original minuta, contingent upon compliance with formal requirements stipulated in Article 1888 of the Civil Code (BW) and under stringent supervision by Supervisory Council of Notaries.